2020
DOI: 10.1089/ten.tea.2019.0034
|View full text |Cite
|
Sign up to set email alerts
|

Regenerative Repair of Volumetric Muscle Loss Injury is Sensitive to Age

Abstract: In this study, the influence of age on effectiveness of regenerative repair for the treatment of volumetric muscle loss (VML) injury was explored. Tibialis anterior (TA) VML injuries were repaired in both 3-and 18-monthold animal models (Fischer 344 rat) using allogeneic decellularized skeletal muscle (DSM) scaffolds supplemented with autologous minced muscle (MM) paste. Within the 3-month animal group, TA peak contractile force was significantly improved (79% of normal) in response to DSM+MM repair. However, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
16
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 58 publications
2
16
0
Order By: Relevance
“…To investigate the role of 5LO in the process of simultaneous bone and muscle healing, we developed a new surgical model of MSK injury in 5LOKO animals. Despite the importance of in vivo investigation for the comprehension of bone healing, previous rodent models of bone and muscle damage focus their attention exclusively on bone formation (14,74), while the majority of studies of the on MSK healing addresses skeletal muscle (23,75) or bone, but separately (24,39). In our study, we performed a moderated simultaneous bone and muscle surgical damage, with a 1-mm diameter defect in muscle and a 0.5-mm diameter defect in the subjacent bone (Figure 2A), in order to avoid further surgical complications, such as femur fracture in aged animals.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To investigate the role of 5LO in the process of simultaneous bone and muscle healing, we developed a new surgical model of MSK injury in 5LOKO animals. Despite the importance of in vivo investigation for the comprehension of bone healing, previous rodent models of bone and muscle damage focus their attention exclusively on bone formation (14,74), while the majority of studies of the on MSK healing addresses skeletal muscle (23,75) or bone, but separately (24,39). In our study, we performed a moderated simultaneous bone and muscle surgical damage, with a 1-mm diameter defect in muscle and a 0.5-mm diameter defect in the subjacent bone (Figure 2A), in order to avoid further surgical complications, such as femur fracture in aged animals.…”
Section: Discussionmentioning
confidence: 99%
“…Apart from the specificity of each cell type involved in skeletal muscle and/or bone regeneration, general tissue healing postinjury requires an initial and transient inflammatory phase, with release of several cytokines and inflammatory mediators, such as AA-derived signaling lipid mediators released from ciclooxigenase-2 (COX2) and 5-Lipoxygenase (5LO) pathways (22)(23)(24). These processes inherent to the inflammatory response are essential in directing vascular events and leukocytes migration, through the release of PGs and LTs (LTB4 and/or CysLTs), respectively (25,26).…”
Section: Introductionmentioning
confidence: 99%
“…Repair of skeletal muscle involves the complex but coordinated processes of satellite cell activation and proliferation, myoblast proliferation and differentiation, inflammation,and extracellular matrix remodelling (Tidball, 2011). However, following large traumatic loss of muscle tissue, or volumetric muscle loss (VML), the endogenous repair mechanisms of skeletal muscle are overwhelmed, often leading to overt fibrosis and chronic inflammation at the site of injury (Kim et al., 2020). VML results in permanent functional deficits as well as cosmetic deficits (Grogan & Hsu, 2011; Terada et al., 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Chronic inflammation is associated with VML (Nuutila et al, 2017) and increased gene expression of inflammatory modulators have been reported at various time points following VML (Corona et al 2018). Our laboratory has demonstrated elevated expression of inflammatory cytokines TGF-β and interleukin (IL)-1β following VML (Kim et al, 2020). Persistent inflammation inhibits myogenesis and enhances the fibrotic response, which inhibits recovery of skeletal muscle (Perandini et al, 2018).…”
mentioning
confidence: 95%
See 1 more Smart Citation